Coaxial and emulsion electrospinning of extracted hyaluronic acid and keratin based nanofibers for wound healing applications - ŞENGÖR, MUSTAFA; GÜNDÜZ, OĞUZHAN (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Novel composites based on poly(epsilon-caprolactone)/polyethylene oxide loaded with hyaluronic acid(HA) and keratin(KR) were produced separately using emulsion and coaxial electrospinning methods. HA and KR were extracted from animal sources, characterized and loaded into coaxial fiber structures as bioactive agents, separately and together. Morphological, chemical, thermal, and mechanical characteristics of the fibers were investigated. According to the SEM results, diameters of smooth and beadless fibers fabricated via emulsion method were at nanoscale (sub-micron) while fibers of coaxial method were at micro scale. Benefitted electrospinning techniques demonstrated that hydrophobic and hydrophilic polymers can be advantageously combined. Core polymer specific FT-IR bands were not visible, their presence was proven with DSC analysis which confirms core-shell morphology of the fibers. In vitro studies exhibited spun mats did not have any cytotoxic effects and the HA and KR incorporated into the fiber structure synergistically increased cell viability and cell proliferation. This study demonstrated that the electrospun fibers containing HA and KR fabricated by both emulsion and coaxial methods can be efficient for wound healing applications.
Keywords: Hyaluronic acid; Keratin; Emulsion electrospinning; Coaxial electrospinning; Wound healing; DRUG-DELIVERY; ROOSTER COMB; FIBERS; PROLIFERATION; REGENERATION; DRESSINGS; PROMOTION; RELEASE; BURNS; FIELD